Enhancing methane sensing with NDIR technology: Current trends and future prospects - Fu Li; You Shixi; Li Guangjun; Fan Zengchang (Reviews in Analytical Chemistry, 2023)
This study presents an in-depth review of non-dispersive infrared (NDIR) sensors for methane detection, focusing on their principles of operation, performance characteristics, advanced signal processing techniques, multi-gas detection capabilities, and applications in various industries. NDIR sensors offer significant advantages in methane sensing, including high sensitivity, selectivity, and long-term stability. The underlying principles of NDIR sensors involve measuring the absorption of infrared radiation by the target gas molecules, leading to precise and reliable methane concentration measurements. Advanced signal processing techniques, such as single-frequency filtering and wavelet filtering algorithms, have been explored to improve the performance of the sensor by reducing noise, enhancing the signal-to-noise ratio, and achieving more accurate results. In the context of multi-gas detection, NDIR sensors face challenges due to overlapping absorption spectra. However, various solutions, including narrow-band optical bandpass filters, gas filter correlation techniques, and machine learning algorithms, have been proposed to address these issues effectively. This study delves into specific applications of NDIR sensors in various industries, such as coal mines, wastewater treatment plants, and agriculture. In these settings, NDIR sensors have demonstrated their reliability, accuracy, and real-time monitoring capabilities, contributing to environmental protection, safety, and energy recovery. Furthermore, the anticipated future trends and developments in NDIR methane detection technology are explored, including increased miniaturization, integration with artificial intelligence, improvements in power efficiency, and the development of multi-gas NDIR sensors. These advancements are expected to further enhance the capabilities and widespread adoption of NDIR sensors in methane detection applications.